Fertility after Transcatheter Arterial Embolization for Obstetric Hemorrhage: An Urban Health Care System Observational Study - Mills, Ariana C.; Marinelli, Brett; Klein, Emma D.; Garcia-Reyes, Kirema; Shilo, Dan; Nowakowski, Scott; Patel, Rahul; Patel, Rajesh; Kim, Edward; Fischman, Aaron; Bishay, Vivian; Loudon, Holly; Stone, Joanne; Lookstein, Robert (American Journal of Perinatology, 2023)
Objective This study aimed to investigate pregnancy rate, pregnancy outcomes, and resumption of menses after transcatheter arterial embolization (TAE) for obstetric hemorrhage (OH).Study Design Sixty-seven patients who underwent TAE for OH from 2006 to 2020 within an urban, multihospital health care system were identified retrospectively. Selected patients were interviewed by phone to complete a survey with a primary outcome of self-reported pregnancy in those seeking pregnancy. Secondary outcomes included pregnancy outcomes and resumption of menses. Univariate testing of association of pregnancy and miscarriage rate with embolic agent was performed using Fisher's exact test.Results Thirty-three of 50 patients (66%) meeting the inclusion criteria completed the survey on fertility, a median of 47 (range, 13–123) months after TAE for OH. Of the 13 patients who attempted pregnancy, there was a pregnancy rate of 77% and miscarriage rate of 38%. Those who delivered live newborns conceived spontaneously, carried to term, and delivered a healthy newborn via cesarean section at a weight appropriate for gestational age. Thirty (91%) patients resumed menstruation, and the majority with unchanged frequency. Most patients underwent bilateral uterine artery embolization with radial artery access (54%). The most common embolic agents used were gelfoam only (30%) and glue only (24%). There was no statistically significant association between embolic agent and pregnancy or miscarriage rate.Conclusion Spontaneous pregnancy with live birth and resumption of menses can occur in a majority of patients after TAE for OH.Key Points
Keywords: postpartum; obstetric; hemorrhage; embolization; fertility